The effect of NPK Compound (6:16:7) on Chemical Soil Properties of Thapic Epiaquands and Cucumber Yield - . Sukristiyonubowo; Ibrahim Adamy Sipahutar; Ishak Achmad (UNIVERSITY OF LAMPUNG, 2009)
The effect of NPK compound (6:16:7) on chemical soil properties of Thapic Epiaquands, growth and yield of cucumber (Cucumis sativus) has been studied in Punthuk Rejo Village, Karanganyar District. The aims were to study the influence of NPK fertiliser on chemical soil properties, growth and yield of cucumber. The treatments were arranged in Randomized Complete Block Design and replicated three times. The treatments were rate of NPK fertilisers including control, NPK standard, 150 kg NPK compound (6:16:7) ha-1, 300 kg NPK compound (6:16:7) ha-1, 450 kg NPK compound (6:16:7) ha-1, 600 kg NPK compound (6:16:7) ha-1, 300 kg NPK compound (6:16:7) ha-1 + ¼ NPK standard, and 300 kg NPK compound (6:16:7) ha-1 + ½ NPK standard. The NPK standard originated from single fertiliser, namely urea, SP-36 and KCl, while the NPK compound was Agrotop, containing 6.15% N, 16.23% P2O5 and 6.87% K2O following named NPK compound (6:16:7). The rate of NPK standard was 100 kg urea ha-1, 100 kg SP-36 ha-1 and 200 kg KCl ha-1 referring to the local recommended fertiliser rate. Application of NPK, both NPK (6:16:7) and NPK Standard, improved the chemical soil properties, namely N, P and K total as well available P. So far, application of 300 kg NPK compound ha-1 significantly increased the number of cucumber fruits and cucumber yield. Compared to the control, the increases were 13% and 44% for the number of cucumber fruits and cucumber yield, respectively. So far, combination of NPK compound (6:16:7) at the rate of 300 kg ha-1 with half recommended rate of NPK standard yielded a significant effect on both the number of cucumber fruits and weight of cucumber. These improvements were comparable to the NPK standard under fully recommended rate. The relative agronomic effectiveness value of combination of NPK (6:16:7) at the rate of 300 kg ha-1 with half recommended rate of NPK standard were about 100%, similar with the value of NPK standard. The economic analysis indicated that NPK standard with recommended application rate and combination of NPK Agrotop at the rate of 300 kg ha-1 with half recommended rate of NPK standard gave high benefit, B/C ratio and IBCR. The B/C ratio and IBCR were higher than one.